Urgensi pokok-pokok ajaran Islam pada anak usia dini, remaja dan dewasa - Al Ansori, Zul (Maliki Interdisciplinary Journal, 2024)
The values of Islamic teachings are the essence of the teachings of Islam itself, the main teachings of Islam include the science of monotheism and the science of aqidah, jurisprudence and morality. Knowing the science of monotheism and aqidah will strengthen the belief of a Muslim as well as studying the science of fiqh which regulates worship and muamalah, will make a Muslim know the correct procedures for worship and muamalah. The science of morality is no less important because studying it will make a Muslim ethical, moral and civilized. In order to realize a superior Islamic generation, education and teaching of the main teachings of Islam must be applied to various groups, both in early childhood, youth and adults, through instilling the basic values of Islamic teachings in various groups, especially the younger generation, it is hoped that the nation, This country and religion experienced major changes in the progress of civilization as a result of a qualified young generation adhering to the teachings of Islam.